Functional assessment of allelic variants in the SLC26A4 gene involved in Pendred syndrome and nonsyndromic EVA - Pera, Alejandra; Dossena, Silvia; Rodighiero, Simona; Gandía, Marta; Bottà, Guido; Meyer, Giuliano; Moreno, Felipe; Nofziger, Charity; Hernández-Chico, Concepción; Paulmichl, Markus (Proceedings of the National Academy of Sciences - PNAS, 2008)
Pendred syndrome is an autosomal recessive disorder characterized by sensorineural hearing loss, with malformations of the inner ear, ranging from enlarged vestibular aqueduct (EVA) to Mondini malformation, and deficient iodide organification in the thyroid gland. Nonsyndromic EVA (ns-EVA) is a separate type of sensorineural hearing loss showing normal thyroid function. Both Pendred syndrome and ns-EVA seem to be linked to the malfunction of pendrin (SLC26A4), a membrane transporter able to exchange anions between the cytosol and extracellular fluid. In the past, the pathogenicity of SLC26A4 missense mutations were assumed if the mutations fulfilled two criteria: low incidence of the mutation in the control population and substitution of evolutionary conserved amino acids. Here we show that these criteria are insufficient to make meaningful predictions about the effect of these SLC26A4 variants on the pendrin-induced ion transport. Furthermore, we functionally characterized 10 missense mutations within the SLC26A4 ORF, and consistently found that on the protein level, an addition or omission of a proline or a charged amino acid in the SLC26A4 sequence is detrimental to its function. These types of changes may be adequate for predicting SLC26A4 functionality in the absence of direct functional tests.